Total Zn of foods and bioaccesible fractions in the small and large intestine after in vitro digestion and fermentation with fecal material of healthy adults and children: Influence of culinary techniques - García-Conde, Úrsula; Navarro-Alarcón, Miguel; Navajas Porras, Beatriz; Hinojosa-Nogueira, Daniel; Delgado-Osorio, Adriana; Pérez-Burillo, Sergio; Pastoriza, Silvia; Navarro-Moreno, Miguel; Rufián-Henares, José Ángel (Elsevier, 2023)
The healthy status of human beings is associated with an appropriate nutritional status in Zn, which must firstly be bioavailable. We measured the total Zn amount and its bioaccesibility in raw foods and after cooking by common culinary techniques. These foods were submitted to an in vitro digestion and fermentation with faecal inocula from healthy adults and children to evaluate Zn bioaccesibility in the small and large intestine. Mean total Zn amount provided by foods was 8.080 μg/g. Zn amount released from food in the small intestine was significantly different among several food groups and lower in raw vegetal foods compared to cooked ones (frying, roasting and grilling; p < 0.05); the same behaviour was found in the large intestine for healthy children. Zn bioaccesibility in the large intestine varied statistically according to the subjects’ idiosyncrasies, and was higher in healthy children (p < 0.05) probably due to growth demands and different composition of the colonic microbiota. In healthy adults and children, the bioaccesible fractions were 33.0 ± 20.4 % for the small intestine, 16.4 ± 22.0 and 59.6 ± 29.9% for the large one, and the non-bioaccessible ones 50.6 ± 19.9 and 7.4 ± 9.1%, respectively.
Keywords: Flora intestinal - Investigación; Cinc; Zinc; Zn bioaccesibility; Healthy adults; Healthy children; Culinary techniques